Development and characterisation of a panel of phosphatidylinositide 3-kinase – mammalian target of rapamycin inhibitor resistant lung cancer cell lines - Susan Heavey (Scientific Reports, 2018)
Abstract The PI3K-mTOR pathway is involved in regulating all hallmarks of cancer, and is often dysregulated in NSCLC, making it an attractive therapeutic target in this setting. Acquired resistance to PI3K-mTOR inhibition is a major hurdle to overcome in the success of PI3K-mTOR targeted agents. H460, A549, and H1975 resistant cells were generated by prolonged treatment in culture with Apitolisib (GDC-0980), a dual PI3K-mTOR inhibitor over a period of several months, from age-matched parent cells. Resistance was deemed to have developed when a log fold difference in IC50 had been achieved. Resistant cell lines also exhibited resistance to another widely investigated PI3K-mTOR dual inhibitor; Dactolisib (BEZ235). Cell lines were characterised at the level of mRNA (expression array profiling expression of >150 genes), miRNA (expression array profiling of 2100 miRNAs), protein (bottoms-up label-free mass spectrometry) and phosphoprotein (expression array profiling of 84 phospho/total proteins). Key alterations were validated by qPCR and Western blot. H1975 cells were initially most sensitive to Apitolisib (GDC-0980), but developed resistance more quickly than the other cell lines, perhaps due to increased selective pressure from the impressive initial effect. In-depth molecular profiling suggested epithelial-mesenchymal transition (EMT) may play a role in resistance to PI3K-mTOR dual inhibition in NSCLC.